Pengaruh Layanan Bimbingan Kelompok dengan Metode Permainan Terhadap Penerimaan Diri Siswa Kelas X SMAN I BABELAN: Layanan Bimbingan kelompok dengan metode permainan terhadap penerimaan diri - Sitorus, Muhammad Walimsyah (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2019)
This study aims to determine the effect of game methods with group guidance services on student self-acceptance. The research method used was a Quasi experimental design nonequivalent control group design. The experimental group received treatment in the form of 11 group counseling sessions held twice a day. The control group did not receive treatment. The population in this study was the students of class X SMAN I Babelan in the year of 2018. The sampling technique used was purposive sampling. The students who became the sample in this study were 20 people with self-acceptance scores in the low category. The instrument used in determining the sample of this study was a self-acceptance instrument with four choices in the Likert scale model consisting of 36 valid items with reliability using Cronbach's alpha of 0.735. Hypothesis testing results indicate that the Asymp value. Sig of 0.005, through the calculation results, the conclusion was obtained on the self-acceptance of students sig <0.05, meaning that the increase in self-acceptance of students of class X SMAN I Babelan treatment group was higher than the control group. Based on the results of the study it is expected that the teacher's guidance and counseling at the school to conduct group guidance service activities with the game method of student self-acceptance